E-021 Acute Interventional Treatment of Atherosclerotic Carotid Occlusion and Intracranial Thromboembolism. (14th July 2013) - Heck, D; Brown, M
Abstract : The patient presenting with acute carotid occlusion and intracranial embolism poses additional challenges compared with the patient with intracranial embolism and no cervical carotid obstruction. There are technical challenges of gaining access to the intracranial circulation for thrombolysis or embolectomy and decisions regarding pharmacologic management after placing a stent in an acutely occluded vessel, all of which may lead to additional complications. We report 18 consecutive cases of acute carotid occlusion or near occlusion treated in the last two years. Outcomes and procedural details were collected prospectively in our interventional stroke database. No patients have been lost to follow up. The mean age is 68 (median 65, range48–86). The mean NIHSS is 19 (median 19, range 9–26). Guidewire access was gained across the occlusion in all patients. In one patient stenting was not technically possible (only angioplasty) due to heavy calcification of the vessel, and in one patient the carotid terminus could not be opened after stenting of the cervical carotid occlusion. Normal flow was reestablished in the other 16 extracranial carotid arteries after stenting (89%). The 90 day mortality was 33%, with 3 cases of fatal haemorrhage (17%), all of which occurred in the first 24 hours. Favourable outcomes at 90 days (MRS 0–2) were obtained in 10 patients (55%), two of whom had favourable outcomes despite failed revascularisation of the middle cerebral artery after successful carotid stenting to improve inflow to pial collaterals. Overall, TICI 2B or greater flow was obtained in the middle cerebral artery in 14 patients (78%), TICI 2A or greater in 15 (83%). There was no embolisation to previously uninvolved territories (anterior cerebral artery or opthalmic artery). There were no delayed occlusions of carotid stents in patients who survived the initial stroke (n=12), and just one case of moderate restenosis at 6 months. In summary, favourable clinical outcomes and mortality in this cohort of patients treated with extracranial carotid stenting combined with intracranial embolectomy or thrombolysis for extracranial carotid occlusion and large vesse intracranial occlusion are similar to our patients who did not have extracranial carotid obstruction. However, the incidence of symptomatic haemorrhage is higher. We will compare the above results with our overall results and discuss technical aspects and strategies for anti-platelet therapy in this situation. Disclosures: D. Heck: None. M. Brown: None.